2015
DOI: 10.1093/jamia/ocv011
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations to improve the usability of drug-drug interaction clinical decision support alerts

Abstract: DDI clinical decision support alerts need major improvements. We provide recommendations for healthcare organizations and IT vendors to improve the clinician interface of DDI alerts, with the aim of reducing alert fatigue and improving patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
165
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(174 citation statements)
references
References 41 publications
2
165
1
1
Order By: Relevance
“…The above issues reflect the lack of gold standard and consensus that have been called for by several author groups [21,22,41,42]. While implementation of the suggestions made to standardization of evaluation of evidence and clinical consequences may resolve some of the discrepancies the importance of transparency cannot be underestimated [21][22][23]43].…”
Section: Discussionmentioning
confidence: 99%
“…The above issues reflect the lack of gold standard and consensus that have been called for by several author groups [21,22,41,42]. While implementation of the suggestions made to standardization of evaluation of evidence and clinical consequences may resolve some of the discrepancies the importance of transparency cannot be underestimated [21][22][23]43].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the problem of alert fatigue, in addition to creating user dissatisfaction, is that it causes users to ignore serious alerts and endangers patient safety [89,90]. Hence, many articles [89,91] focused on CDSS-related studies in other areas on assessing the quality of alerts provided in the CDSS and evaluating the effectiveness of these alerts. Effectiveness assessment of alerts designed in chemotherapy prescription CDSS is highly significant for continuous improvement of these systems and user satisfaction enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…The survey provided optional responses for resources, keywords, and study types that were identified from the team's prior research on the information needs of professionals who search and synthesize PDDI evidence [11]. Questions about PDDI information search were organized according to the range of PDDI topics important for clinical decision making recently published by Payne et al [29]. Two of the survey questions provided open-ended responses that participants could use to provide additional comments as well as share search terms that they find useful.…”
Section: Methodsmentioning
confidence: 99%